Evaluation of changes in liver functions of normal pregnant women in Shendi locality, Sudan - Hummieda, Sami; Eltigani, Mohammed A; Al Deen, Babiker Gamal; AL Baz, Hanaa (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Changes in value of certain serum liver function tests occur during normalpregnancy and an understanding of these physiological changes is necessary for the managementof liver diseases.Material & Methods: This cross-sectional study was conducted at Shendi locality. Thepatients underwent a clinical assessment, which included history (a questionnaire) and clinicalexamination. 160 women were divided into four group’s non pregnant as control group, 1st, 2ndand 3rd trimester of pregnancy respectively. The age limits was 12 to 40 years. Serum sample wastaken and assessed for routine liver function tests.Results: All values were within normal limits. Serum ALT and AST activity was slightlydecreased (not significant) in first, second and third trimester than control pregnant women. Themean value of serum total, direct and in direct bilirubin concentrations were also slightlydecreased (not significant) in first and second trimester than control but increased thirdtrimester pregnant women.Conclusion:It concluded that the serum ALT, AST and total bilirubin are affected by pregnancy in the3rdtrimester more than the1st trimester.